PELAKSANAANSISTEM MERIT DALAM UU ASN, WEWENANG KASN DAN ANALISIS PERATURAN PERUNDANG-UNDANGAN YANG BERPENGARUH TERHADAP WEWENANG KASN - WAWANUDIN WAWANUDIN; ROHIDIN SUDARNO (iLearning Journal Center, 2018)
ABTRACTLaw No. 5 of 2014 concerning ASN is a new approach in ASN management. In its journey, the ASN Law is in the process of revision in the DPR. This study aims to 1. Undertsand the main discussion in the revision of the law relating to the implementation of the merit system in the determination of JPT and the presence of honorary workers and PPPK. 2. Analyse the implementation of KASN authority 3. Highlight the description of the laws and regulations that are perceived to be influencing the implementation of KASN authority. This study uses qualitative methods and data collection techniques that are carried out through desk research (desk study) especially collecting data and information through available relevant public sources (secondary data). There are three conclusions obtained from this research; 1). A discussion on the implementation of ASN Law referring to the revision of ASN Law in terms of the requirements of further regulation regarding; a. JPT Promotion and Selection, b. Existence of Honorary Personnel and PPPK, c. Implementation of the Authority of the National Civil Service Committee (KASN) and d. the need to breach the gaps specifically with the fate of K2 and Honorer Region 2). The Implementation of the KASN Authority is generally good enough, although there are still problems. However, KASN does ensure that the merit system continues to run according to the objectives of the ASN Law. In terms of indicators of the implementation of selection, complaint resolution and quality indicators for the implementation of open selection indicate that KASN has worked, and 3). There are five other laws and regulations that affect the implementation of the ASN Law.Keywords: Revision, KASN, PPPK, ASN, JPT.ABSTRAKUndang-undang Nomor 5 tahun 2014 tentang ASN merupakan pendekatan baru dalam manajemen ASN. Dalam perjalannya, UU ASN tengah dalam proses revisi di DPR. Penelitian ini bertujuan untuk 1. Mengetahui bahasan utama dalam wacana Revisi UU terkait dengan penerapan sistem merit dalam penetapan JPT, keberadaan tenaga honorer dan PPPK. 2. Menganalisis pelaksanaan wewenang KASN 3. Mengetahui gambaran peraturan perundang-undangan yang dipandang mempengaruhi pelaksanaan wewenang KASN. Penelitian ini menggunakan metode kualitatif dan teknik pengumpulan datanya dilakukan melalui penelitian pustaka (desk study) yaitu cara pengumpulan data dan informasi melalui sumber-sumber yang tersedia di publik (data sekunder) yang relevan. Kesimpulan yang diperloleh dari penelitian ini adalah; 1). Bahasan permasalahan pelaksanaan UU ASN yang mewacanakan Revisi UU ASN dan masih memerlukan pengaturan lebih lanjut adalah; a. Promosi dan Seleksi JPT, b. Keberadaan Tenaga Honorer dan PPPK, c. Pelaksanaan Kewenangan Komisi Aparatur Sipil Negara (KASN) d. perlu pendekatan untuk menjembatani secara khusus nasib K2 dan Honorer Daerah 2). Pelaksanaan Kewenangan KASN secara umum cukup baik, meski masih ada catatan. KASN memastikan sistem merit tetap berjalan sesuai tujuan UU ASN. Indikator pelaksanaan seleksi, penyelesaian aduan dan indikator mutu pelaksanaan seleksi terbuka menunjukan bahwa KASN telah bekerja, dan 3). Terdapat lima peraturan perundangan lain yang mempengaruhi pelaksanaan UU ASN. Kata kunci: Revisi, KASN, PPPK, ASN, JPT.